157 WHOLE HIPPOCAMPAL VOLUMES AND HIPPOCAMPAL SUBFIELD VOLUMES IN MCI-LB AND MCI-ad. (18th November 2021) - Durcan, R; Colloby, S J; Donaghy, P C; Lawley, S; Taylor, J-P; O'Brien, J T; Thomas, A J
Abstract: Background: Mild cognitive impairment with Lewy bodies (MCI-LB) is the commonest prodromal phenotype of Dementia with Lewy Bodies (DLB) and may be challenging to differentiate from MCI due to Alzheimer's disease (MCI-AD). Preservation of medial temporal lobe structures on MRI is recognised as a supportive biomarker consistent with underlying Lewy body disease rather Alzheimer's disease (AD). We investigated whether whole hippocampal volume and differing hippocampal subfield atrophy patterns, could be used as a surrogate biomarker of underlying ad pathology, allowing for differentiation of MCI-LB from MCI-AD. Methods: Participants were recruited to the following groups': healthy controls (HC), MCI-LB and MCI-ad, all ≥60 years. Alongside detailed clinical, neuropsychological assessments, all participants underwent 3 T MRI, 123 I-FP-CIT SPECT and 123 I-MIBG myocardial scintigraphy. Using Freesurfer (v.6.0), a fully automated hippocampal subfield segmentation of the MRI data was performed. Results: Groups consisted of 31 HC (mean age, 73.7 yrs; mean Mini-Mental state Examination [MMSE] score, 28.4), 34 MCI-LB ( mean age, 74.7 yrs; mean MMSE score, 26.6 ) and 29 MCI-ad ( mean age, 75.4 yrs; mean MMSE score, 27.1 ). There was no significant difference in whole hippocampal volume between MCI-LB and MCI-ad (Mean (SD) in mm 3 : MCI-LB 6025 (961) vs MCI-ad 5407 (882), p = 0.12) or between MCI-LB and HC (Mean (SD) in mm 3 : MCI-LB 6025 (961) vs HC 6355 (962), p = 0.11) . Whole hippocampal volume was significantly smaller in MCI-ad compared with HC (p < 0.001) . Comparison between MCI-LB and MCI-ad, showed absolute hippocampal subfield volumes were all lower in MCI-ad . However, the magnitude of the differences were small and no significant difference in hippocampal subfield volumes were noted between these groups, with the exception of the hippocampal tail being significantly smaller in MCI-ad compared to MCI-LB (p = 0.04) . Conclusion: In a well-characterised cohort, whole hippocampal and hippocampal subfield volumes were similarly atrophied in MCI-LB and MCI-ad and did not distinguish between the groups.